Kontribusi Ibu Rumah Tangga Pekerja di Desa Non pertanian dan Desa Pertanian terhadap Pendapatan Rumah Tangga (Studi Kasus di Desa Beraban, Kecamatan Kediri dan Desa Wongaya Gede, Kecamatan Penebel, Kabupaten Tabanan) - MADE WAHYU LESTARI; KETUT BUDI SUSRUSA; NI WAYAN PUTU ARTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Contribution Made by the Employed Housewives Living at Agricultural andNon-agricultural Villages to Their Family Income(A Case Study Conducted at Beraban Village, Kediri District and Wongaya GedeVillage, Penebel District, Tabanan Regency)The faster economic growth leads to multiple effect and inspires different economicactivities which can absorb and cause housewives to have access to job opportunities.However, the job opportunities available at the agricultural village are different fromthose available at the non-agricultural village. As a consequence, the contribution madeby the housewives living at the agricultural village to the family income is differentfrom that made by those living in the non-agricultural village. This current study wasintended to (1) identify the extent to which the housewives living at the agriculturalvillage and non-agricultural village can contribute to the family income; (2) whatmotivated the housewives to work; and (3) what obstructed the housewives in theiremployment. This present study was conducted from July to August 2017 at BerabanVillage, Kediri District, and at Wongaya Gede Village, Penebel District. The sampleswere taken using the Multistage Random Sampling, and totaled 77. The data wereanalyzed using the quantitative descriptive analysis, different test, and descriptivequalitative analysis. The result of the study shows that (1) the contribution made by thehousewives living at the non-agricultural village was smaller than that made by thoseliving at the agricultural village; (2) spare time inspired most of the housewives living atthe non-agricultural village to work; (3) the household chores such as looking after theirhouses, taking care of their children, and the family members who were sick, and soforth obstructed them in their employment. Therefore, it is suggested to the housewivesboth living at the agricultural village and non-agricultural village to collaborate with therelated institutions as an attempt to improve their productivity and efficiency inorganizing their time.